ANALISIS KURIKULUM PENDIDIKAN LINGKUNGAN HIDUP PADA SEKOLAH DASAR PEKANBARU - Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
The purpose of this research is to create equal distribution and understanding of life area education for primary school students, so that students can develop appropriate attitudes and actions in accordance with the concept of life area education. In addition, this research aims to provide an alternative model for the development of life area education in Pekanbaru based on the national curriculum or local curriculum, so that it can contribute concretely to curriculum development within the framework of life area education. The data used in this research consisted of primary and secondary data. Primary data were obtained through surveys in the form of direct observations in schools and interviews with relevant stakeholders, including the Head of the Education Department, school principals, and teachers. Primary data were also collected through questionnaires distributed to principals, teachers, and students, focusing on cognitive, affective, and psychomotor aspects of life area education. Secondary data were obtained from school-related documents, such as records of environmental education (PLH) activities conducted in schools, as well as documents from relevant stakeholders. Based on the analysis of the school curriculum, life area education can be integrated into five subjects: religion, civics, science and technology, arts, and physical education. Furthermore, the analysis of educational stakeholders indicates strong support for the inclusion of life area education in the local curriculum and its implementation in daily school activities. Based on the analysis of students’ knowledge and attitudes, primary school students demonstrate a good understanding of life area education and have shown positive behaviors in caring for their school environment.